Model Project Based Learning berbantuan 3D Maps materi pola aliran sungai: Pengaruhnya terhadap kemampuan berpikir spasial siswa SMA - Nur Hidayanti; Hadi Soekamto; Heni Masruroh (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, 2023)
The fundamental skill in learning Geography is the ability to think spatially. The Project-Based Learning (PjBL) model assisted by 3D Maps makes it easier for students to utilize knowledge and understanding of the material as a medium to improve spatial thinking. The purpose of this study was to determine the effect of the PjBL model with the aid of 3D Maps on the material of river flow patterns on the spatial thinking skills of high school students. This research uses a quasi-experiment method. Consisted of 70 students as research subjects with details of 35 students in the experimental class and 35 students in the control class. The results showed that there was an increase in students' spatial thinking skills, where the experimental class was higher than the control class. The PjBL model with the help of 3D Maps material on river flow patterns has a positive impact on the spatial thinking skills of high school students. The researcher also compared the students' average post-test scores by gender. The results show that female students get better average scores than male students. Many factors affect the difference in the level of thinking of men and women, including: spatial experiences, environmental factors, and emotional differences. Keterampilan fundamental dalam pembelajaran Geografi yaitu kemampuan berpikir spasial. Model Project Based Learning (PjBL) berbantuan 3D Maps mempermudah siswa dalam memanfaatkan ilmu pengetahuan dan pemahaman materi sebagai media meningkatkan berpikir spasial. Tujuan dari penelitian ini yaitu untuk mengetahui pengaruh model PjBL berbantuan 3D Maps materi pola aliran sungai terhadap kemampuan berpikir spasial siswa SMA. Penelitian ini menggunakan metode quasy experiment. Terdiri dari 70 siswa sebagai subyek penelitian dengan rincian 35 siswa kelas eksperimen dan 35 siswa kelas kontrol. Hasil penelitian membuktikan terjadi peningkatan kemampuan berpikir spasial siswa, dimana kelas eksperimen lebih tinggi dibandingkan kelas kontrol. Model PjBL berbantuan 3D Maps materi pola aliran sungai memberikan dampak positif terhadap kemampuan berpikir spasial siswa SMA. Peneliti juga membandingkan nilai rata-rata post-test siswa berdasarkan gender. Hasilnya menunjukkan bahwa siswa perempuan mendapatkan nilai rata-rata lebih baik daripada siswa laki-laki. Banyak faktor yang mempengaruhi perbedaan tingkat berpikir laki-laki dan perempuan, diantaranya yaitu: pengalaman spasial, faktor lingkungan dan perbedaan emosi.